Magnitudes of diseases in dogs vary among different levels of age, gender, breed, and season: A hospital-based, retrospective cross-sectional study - Mohammod Misbah Uddin (Elsevier, 2021)
Dogs, the most common companion animal of humans, perform not only the auxiliary of an individual, but also contribute to the nations’ crime and defence departments. Knowing the determinant-based disease status of dogs is imperative to keep them healthy by subsequent prevention and control of those diseases; however, such baseline epidemiological information is limited. Therefore, a retrospective cross-sectional study was conducted to estimate the proportional incidence of dog diseases to explore their magnitudes, and we compared them to different levels of intrinsic (age, gender, breed) and extrinsic determinants (season). Purposively, data of a total of 1,557 cases of different diseases were collected from the record book of the Central Veterinary Hospital (CVH), Dhaka, Bangladesh. The proportional incidence was calculated as the proportion of cases of a specific disease among total number of cases of all types of diseases attended the hospital during the study period. Diseases of dog were categorized into infectious, non-infectious, and non-specific. Results showed that the highest proportional incidence was noted in infectious diseases (53.8%) followed by non-infectious diseases (23.4%) and the lowest in non-specific (22.7%) cases. Among them, disease-specific proportional incidence was remarkable in case of mange (9.5%), parvovirosis (8.7%), lacerated wound (8.5%), ectoparasitism (8.3%), helminthiasis (7.8%), and fracture (5.7%). The occurrence of mange varied significantly (p < 0.05) among all studied determinants (age, gender, breed, and season); while significant discrepancies (p < 0.05) in magnitudes of lacerated wound, dystocia, abortion, and gastroenteritis were observed among various groups of age, gender, and breed. Accordingly, dermatitis and orchitis had significant differences (p < 0.05) in proportional incidence amid various levels of age, gender, and season; whilst the burden of parvovirosis and alopecia differed significantly (p < 0.05) amongst different categories of age, breed, and season. The magnitude of otorrhoea showed a significant (p < 0.05) variation among different groups of gender, breed, and season. The proportional incidence of other diseases also varied significantly (p < 0.05) amongst either one or two studied determinants. This study provides a valuable insight about important diseases in dogs, which may serve as useful baseline information for disease prioritization and subsequent planning of effective control and prevention measures against those diseases.